2019
DOI: 10.1128/jcm.00963-19
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Nanopore Sequencing of Influenza Virus Direct from Clinical Respiratory Samples

Abstract: Influenza is a major global public health threat as a result of its highly pathogenic variants, large zoonotic reservoir, and pandemic potential. Metagenomic viral sequencing offers the potential for a diagnostic test for influenza virus which also provides insights on transmission, evolution, and drug resistance and simultaneously detects other viruses. We therefore set out to apply the Oxford Nanopore Technologies sequencing method to metagenomic sequencing of respiratory samples. We generated influenza viru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 52 publications
7
121
0
1
Order By: Relevance
“…From this study, an advantage of direct RNA sequencing over amplicon sequencing, such as PCR-cDNA, was that DRS showed a quantitative relationship between input viral titers and output sequencing reads. Similarly, a strong relationship between influenza viral titers and influenza sequencing reads using Oxford Nanopore direct RNA sequencing technology was observed by other research groups [ 57 ]. However, in a hepatitis B virus (HBV) study using Oxford Nanopore amplicon sequencing (which includes a PCR step similar to our PCS protocol), considerable variability in total yields and the proportion of mapped HBV reads between sequencing runs was observed concluding that it was not quantitative [ 59 ].…”
Section: Discussionsupporting
confidence: 68%
“…From this study, an advantage of direct RNA sequencing over amplicon sequencing, such as PCR-cDNA, was that DRS showed a quantitative relationship between input viral titers and output sequencing reads. Similarly, a strong relationship between influenza viral titers and influenza sequencing reads using Oxford Nanopore direct RNA sequencing technology was observed by other research groups [ 57 ]. However, in a hepatitis B virus (HBV) study using Oxford Nanopore amplicon sequencing (which includes a PCR step similar to our PCS protocol), considerable variability in total yields and the proportion of mapped HBV reads between sequencing runs was observed concluding that it was not quantitative [ 59 ].…”
Section: Discussionsupporting
confidence: 68%
“…By comparing, the consensus sequences produced by the described protocol with previously published sequences produced using the other sequencing techniques; we were able to evaluate the performance of the protocol. Other comparisons of the minION sequencing technique to other more traditional, and labor and equipment intensive have equally found that the method produces high quality sequences (29).…”
Section: Discussionmentioning
confidence: 97%
“…We extracted RNA for whole genome sequencing of the viral isolate. Briefly, RNA was extracted from clarified cell culture supernatant and randomly amplified cDNA prepared by sequence‐independent single‐primer amplification (SISPA) . Sequencing was performed with a combination of Oxford Nanopore Technologies and Illumina short‐read sequencing.…”
Section: Methodsmentioning
confidence: 99%